An iterative learning control approach to sensor fault-tolerance in Takagi-Sugeno systems - Pazera, Marcin; Sulikowski, Bartłomiej; Witczak, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a solution to the problem of effective control of a system that is affected by both sensor faults and disturbances (and noises). It is assumed that the model of the system is given in the form of a fuzzy Takagi-Sugeno system. The main goals of the designed control scheme are: achieving a prescribed reference signal at the output, minimizing the impact of disturbances and the ability to respond to faults affecting the system sensor.
Keywords: fault-tolerant control; iterative learning control; sensor faults; Takagi-Sugeno systems